Contribution of naturally durable wood to the circular economy - Yamamoto, Koichi (Acta silvae et ligni, 2025)
Total wood demand is projected by the FAO to increase by 49% between 2020 and 2050, despite deteriorating supply conditions such as deforestation and degradation due to fire and biological damage to forests. Service life extension and reuse of wood can help to mitigate this projected gap between supply and demand. Common construction timber species with moderately durable heartwood include Scots pine, Douglas fir and Japanese cedar. However, this durability varies widely among clones, growing sites and within tree trunks. The selection and utilization of highly durable clones or individuals within these timber species could contribute to extending the service life of building and civil engineering structures that are at greater risk of biodegradation, such as building façades and landscape engineering applications. The authors would like to advance the discussi- on on measures to utilize this selected timber with higher durability, including maintenance strategies and the complementary use of treated timber within the circular economy.
Keywords: carbon storage; circular economy; heartwood; jedrovina; krožno gospodarstvo; laboratorijski test odpornosti; laboratory decay test; naravna odpornost; natural durability; service life; shranjevanje ogljika; standard; standardi